COMPARATIVE ANALYSIS OF INFARCT VOLUMES IN PERMANENT AND TRANSIENT MCAO MODELS USING TTC STAINING: A REVIEW OF CURRENT RESEARCH AND FUTURE DIRECTIONS - Buana, Gherriandi Raja; Makkiyah, Feda Anisah; Wahyudi, Dhyani Paramita (The Health Researcher's Journal, 2025)
Ischemic stroke research often relies on animal models to understand the pathological processes underlying brain injury. Among the most widely used models are permanent middle cerebral artery occlusion (pMCAO) and transient middle cerebral artery occlusion (tMCAO), both of which simulate ischemic events in the brain. However, while existing studies have compared the effects of pMCAO and tMCAO on infarct volumes, many have been limited by short observation periods (e.g., 4 hours) or have focused only on non-occlusion models. This literature review aims to evaluate the comparative effectiveness of these two models in generating infarct sizes, specifically utilizing triphenyltetrazolium chloride (TTC) staining to measure infarct volumes. Our analysis highlights the variability in infarct volumes between the two models and emphasizes further research incorporating longer observation intervals (e.g., 6, 18, and 24 hours). This gap in research is crucial for refining experimental stroke models and improving the clinical relevance of findings, particularly regarding therapeutic strategies for ischemic stroke. The review also suggests potential research pathways to enhance model standardization and consistency in future studies, aiming for more accurate and reproducible results that will inform the development of effective stroke treatments.